EFFECT OF FENOFIBRATE AND GEMFIBROZIL IN SODIUM NITRITE-INDUCED ANTEROGRADE AMNESIA IN MALE WISTAR RATS - SHUJAUDDIN; HASHILKAR, NAYANA K.; MISHRA, SANJAY KUMAR; ANSARI, ZAFAR MASOOD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The present study was planned to study the effect of fenofibrate and gemfibrozil on sodium nitrite-induced anterograde amnesia in male Wistar rats. Methods: Anterograde amnesia was induced by 75 mg/kg of sodium nitrite in six groups (eight in each group) of male Wistar rats (150–180 g). Fenofibrate (21 mg/kg and 18 mg/kg) and gemfibrozil (108 and 21 mg/kg) were used as test drugs. The paradigm used was Morris water maze, where a hidden platform was kept for the rat to escape from the water. Rats were trained to locate a hidden platform by releasing them into water for 4 times a day for 4 consecutive days. The acquisition of this task was measured by noting the time taken to escape to the platform. On the 6th day of the study, retrieval of this learnt task was measured by noting the time taken to search for the missing hidden platform. The time taken by the rats during the acquisition and retrieval tasks in fenofibrate and gemfibrozil treated groups were measured and compared with disease control group. On the 6th day (retrieval trial), only vehicle (distilled water oral) was administered to the groups. Results: Fenofibrate and gemfibrozil completely ameliorated the anterograde amnesia. The mean escape latency time of both fenofibrate and gemfibrozil administered rats was significantly reduced with respect to sodium nitrite group while, retrieval time increased significantly. However, the same group of rats showed significant retrieval of task memory. Conclusion: In the present study, fenofibrate and gemfibrozil ameliorated chemical hypoxia-induced anterograde amnesia. Both can potentially inhibit oxidative stress induced neurodegeneration at the commonly prescribed clinical doses. In addition to their hypolipidemic effect, they can also prevent modifiable risk factors of chronic neurodegenerative disorders. Further studies are needed to substantiate these findings.